2019
DOI: 10.1002/ejoc.201900798
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and Mechanistic Studies into the Rearrangement of Spirocyclic Indolenines into Quinolines

Abstract: A Density functional theory (DFT) approach has been used to shed light on the mechanism of a recently discovered rearrangement reaction for the conversion of spirocyclic indolenines into cyclopentanone‐fused quinolines. A new base‐mediated variant of this unusual rearrangement reaction has also been developed, that operates at much lower temperatures than those required in the analogous acidic reactions. The DFT study suggests that both the acid and base‐mediated variants proceed via an enol/enolate intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“… 5 Finally, our groups and others have demonstrated that spirocyclic indolenines of the form 3 will rearrange via a one-atom ring expansion reaction 13 to form annulated quinolines, with both acidic and basic reagents able to promote this transformation ( 3 → 4 , Scheme 1 a, step 3). 6 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“… 5 Finally, our groups and others have demonstrated that spirocyclic indolenines of the form 3 will rearrange via a one-atom ring expansion reaction 13 to form annulated quinolines, with both acidic and basic reagents able to promote this transformation ( 3 → 4 , Scheme 1 a, step 3). 6 …”
mentioning
confidence: 99%
“…This manuscript concerns a three-step cascade reaction sequence, starting from indole-tethered ynones 1 (Scheme ). In recent years, ynones of this type have emerged as valuable precursors for the preparation of a diverse array of molecular scaffolds. For example, our groups and others have shown that the activation of the alkyne moiety of 1 promotes efficient dearomatizing spirocyclization , to form medicinally important spirocyclic indolenines 2 ; , this is most commonly done using π-acidic catalysts (especially Ag­(I) species), although Brønsted acids, palladium­(II) complexes, and electrophilic halogenation reagents can also be used ( 1 → 2 , Scheme a, step 1). ,, Our groups have also shown that dearomatization works well on 2-halogenated indoles (i.e., 1 where X = Cl, Br or I) and that the resulting indoleninyl halide products (i.e., 2 where X = Cl, Br or I) can be transformed further via reaction with nucleophiles, or via Pd-catalyzed cross-coupling, to substitute the halide for various other groups ( 2 → 3 , Scheme a, step 2) . Finally, our groups and others have demonstrated that spirocyclic indolenines of the form 3 will rearrange via a one-atom ring expansion reaction to form annulated quinolines, with both acidic and basic reagents able to promote this transformation ( 3 → 4 , Scheme a, step 3) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[310] The stirring of spirocycles 328 or 329 with lithium hexamethyldisilazide under mild conditions, leads to cyclopenta [c]quinolines 330 (Scheme 88). [311,312] The low-temperature process for the preparation of cyclopenta [c] quinolines 330 from spirocycles 328 and 329 may be useful if the substrates contain functional groups that are sensitive to temperature and acidity of the medium. The conversion of spirocycles 328 and 329 into quinolines 330 in high yields can also be carried out by heating them (50-100°C) in the presence of AlCl 3 or CF 3 COOH.…”
Section: Some Transformations Of Spirocyclic Compoundsmentioning
confidence: 99%
“… 5 , 35 Avoiding bis indolemethane formation is therefore a significant challenge, but one we were confident could be overcome by harnessing the unique reactivity of ynones. 3 , 5 , 8 , 9 , 11 , 13 In our previous work, we have shown that the electron-withdrawing carbonyl group of the ynone moiety can significantly enhance the reactivity of the alkyne when treated with a Au(I) catalyst. This enables ynones to be coupled with indoles under very mild conditions.…”
Section: Introductionmentioning
confidence: 99%